Colonial Hospital. Trinidad - Strong (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows the Colonial hospital which dates back to 1858. This two storey building, with its Georgian styled architecture, was designed by Lewis Samuels. The building was constructed on the site of the former British military barracks called Orange Grove.
Colour: Sepia with hues of red, green and yellow; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hospitals--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago